The electrical conductivity and dielectric properties of CI Basic Violet 10 - Mansour, Sh. A.; Yahia, I. S.; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2010)
The electrical and dielectrical properties of C.I. Basic Violet 10 were investigated using both DC and AC measurements. The DC electrical conductivity of the dye exhibited similar behavior to that of organic semiconductors and the mechanism of the AC conductivity the dye can be attributed to correlated barrier hopping, as confirmed by an observed reduction in activation energy. The density of localized states for C.I. Basic Violet 10 was 0.15 x 10(22) to 4.4 x 10(22) eV(-1) cm(-3) over the range of temperatures and frequencies employed. Variation of the dielectric constant with temperature at different frequencies showed a dielectric relaxation peak; with increasing frequency, the intensity of the dielectric relaxation peak decreased and became less pronounced. The obtained results suggest that C.I. Basic Violet 10 is an organic semiconductor and its dielectric relaxation mechanism is temperature-dependent. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Organic semiconductor; Organic dye; Dielectric relaxation